2022
DOI: 10.3390/electronics11132069
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Students’ Continuance Intention to Learn in Blended Environments at University

Abstract: (1) Background: The main goal of this study was to determine the factors that have an influence on the continuance intention to learn in blended environments. (2) Methods: For our study, we created a research model based on the Expectation–Confirmation Model (ECM) and Theory of Planned Behavior (TPB), which involves a total of seven latent constructs and contains a total of eight hypotheses. A total of 301 undergraduate and postgraduate students studying at Humanity Institute of Peter the Great Polytechnic Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 53 publications
2
12
0
Order By: Relevance
“…However, other studies have not applied ANN to predict CI or explain CI (e.g. Baranova et al, 2022;Sreelakshmi and Prathap, 2020;Twum et al, 2023). The utilization of ANN in this study has significantly bolstered its findings.…”
mentioning
confidence: 73%
See 4 more Smart Citations
“…However, other studies have not applied ANN to predict CI or explain CI (e.g. Baranova et al, 2022;Sreelakshmi and Prathap, 2020;Twum et al, 2023). The utilization of ANN in this study has significantly bolstered its findings.…”
mentioning
confidence: 73%
“…Second, Wang et al (2021) found that SAT significantly influenced the CI of online learning during COVID-19. Third, Baranova et al (2022) documented that SAT has a significant influence on CI in a blended-learning university (Table 1). When students perceive the services provided by online learning as satisfactory, they continue using the services.…”
Section: Satisfaction (Sat) and Continuance Intention (Ci)mentioning
confidence: 96%
See 3 more Smart Citations